2022
DOI: 10.3390/ijerph19020939
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture in European Hospitals: A Comparative Mixed Methods Study

Abstract: Background: Poorly organized health systems with inadequate leadership limit the development of the robust safety cultures capable of preventing consequential adverse events. Although safety culture has been studied in hospitals worldwide, the relationship between clinician perceptions about patient safety and their actual clinical practices has received little attention. Despite the need for mixed methods studies to achieve a deeper understanding of safety culture, there are few studies providing comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
23
2
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 63 publications
11
23
2
8
Order By: Relevance
“…The current study findings about staffing across professions are relevant to the context and culture of the health sector in each country in Latin America. Similar to other studies [ 34 , 138 , 139 , 140 ], nurses were more concerned about staffing than physicians. This finding may be explained by most countries having as many or more physicians than nurses per 1000 people, despite nurses being responsible for staffing hospitals for 24 h each day of the year.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The current study findings about staffing across professions are relevant to the context and culture of the health sector in each country in Latin America. Similar to other studies [ 34 , 138 , 139 , 140 ], nurses were more concerned about staffing than physicians. This finding may be explained by most countries having as many or more physicians than nurses per 1000 people, despite nurses being responsible for staffing hospitals for 24 h each day of the year.…”
Section: Discussionsupporting
confidence: 82%
“…In the current review, statistically significant differences were observed during the meta-analysis for the perception of patient safety culture across the different professional groups. Adequate clinical staffing in a hospital is essential for achieving improved clinical outcomes [ 130 , 131 , 132 ] and a more favorable patient safety culture [ 34 , 58 ]. The perception of patient safety has been related to the availability of adequate staffing [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the issue of understaffing in healthcare facilities is a global problem, as many studies have also revealed evidence of poor staffing in many countries. These include research conducted on patient safety culture and associated factors in hospitals in the Jima zone in southwest Ethiopia [ 42 ], Saudi Arabi [ 43 ], Lebanon [ 31 ], Sweden, Spain, Hungary, and Croatia [ 44 ]. This finding was further attested by a logistic regression analysis in the present study, which showed that an increase in the negative perception of staffing composite has the odds of 3.15 to a negative perception of the overall patient safety culture.…”
Section: Discussionmentioning
confidence: 99%